SpeedAr: Arithmetic drills via racing game / Nurul Hidayah Mat Zain … [et al.] - Mat Zain, Nurul Hidayah; Johar, Razuan Harmy; Abdul Aziz, Azlan; Baharum, Aslina; Mohd Yasin, Anita; Abdul Aziz, Siti Rahayu; Ismail, Ismassabah (Division of Research and Industry Linkages, 2017)
Arithmetic is the oldest branch of Mathematics which consists the study of numbers, specifically the properties of the basic traditional operations. According to the previous study, most of the users agree that Mathematics subject is a hard subject and there is lack of enjoyment in practicing arithmetic drills. Therefore, we develop enjoyable arithmetic drills via racing games and we named as a Need for Speed Arithmetic (SpeedAr). The SpeedAr game was implemented Rapid Application Development (RAD).